Jet-Fragmentation Transverse Momentum from Di-Hadrons Correlations in √s_NN = 5.02 TeV Pb-Pb Collisions - Gilbert, Alexander Kevin (2020)
The jets’ transverse structure in Pb-Pb collision system has been studied with jet-fragmentation transverse momentum (jT ) distribution. The data were collected from ALICE experiment at LHC in energy √s_NN = 5.02 TeV per nucleon. The analysis was conducted on centrality classes 0-10%, 10-20%, 20-40%, and 40-60% and trigger particle transverse momentum 3 < pTt < 25 GeV/c. The jT signal shows Gaussian distribution (narrow component) related to non-perturbative hadronization and inverse gamma distribution (wide component) related to quantum chromodynamics (QCD) splitting. The measurement of yield per trigger particle results shows a decreasing trend as pTt grows and the decline becomes sharper from peripheral to central collision, proving the enhancement of low-pT particle production due to high-multiplicity environment in heavy ion collision and jet energy loss inside hot quark-gluon plasma. The width of narrow component is independent of pTt and centrality class, proving that the hadronization is universal process. On the other hand, the width for wide component shows fluctuation over pTt. The results are compared to AMPT 2 simulation, ALICE experiment pp √s = 5.02 TeV and 7 TeV data. The comparison to pp data set shows high-multiplicity environment and medium modification in Pb-Pb, while the comparison to AMPT 2 shows overestimation of minijet parton production at low pTt.